PENGARUH PEMBERDAYAAN DAN PENGAWASAN TERHADAP PERILAKU PEGAWAI DALAM RANGKA MENINGKATKAN KUALITAS PELAYANAN SIUP (STUDI PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA MEDAN) - Monang Sitorus (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2009)
One purpose of the establishment of Local Government Act Number 32 of 2004 is to increase the quality of public services such as permit (SIUP) service. In fact, deviation on the implementation process still occurs between public aspiration (das sollen) and the real services which is provided by the public institutions (das sein). This problem is emerged as a result of discrimination. Based on the observation, it can be found that the implementation of empowering and controlling mechanism toward employeess behaviour is not yet optimally conducted, so that the effort to increase the quality of permit service is still far from what the public would be expected. As a result, the researcher needs to examine and analyse the influence of the empowering and controlling mechanism of employees behavior upon the quality of public service provided by Boardof Industry and Trade of the City of Medan. This research uses the method of explanatory survey with quantitative approach. In terms of sample choices, a sensus technique has been chosen, while a The finding shows the existence of direct and indirect influences of the empowering and controlling mechanism toward the employeess behaviour. Besides, the quality of permit (SIUP)service has been positively and significantly influenced by the employees behaviour. Thus, the result of the research has been proven scientifically. However, the reseacher argues that other variables or factors (epsilon) are also influencing the quality of permit (SIUP) service.